Phenotypic and Functional Characterization of Mesenchymal Stem/Multipotent Stromal Cells From Decidua Parietalis of Human Term Placenta. (September 2016) - Abumaree, Mohamed H.; Abomaray, F. M.; Alshehri, N. A.; Almutairi, A.; AlAskar, A. S.; Kalionis, B.; Al Jumah, M. A.
Mesenchymal stem/multipotent stromal cells (MSCs) from the human placenta show stem cell-like properties useful for regenerative medicine. Previously, we reported that MSCs isolated from the fetal part of human term placentae have characteristics, which make them a potential candidate for regenerative medicine. In this study, we characterized MSC isolated from the maternal part of human term placenta. The MSCs were isolated from the decidua parietalis (DPMSCs) of human placenta using a digestion method and characterized by colony-forming unit assay and the expression of MSC markers by flow cytometry technique. In addition, DPMSC differentiation into the 3 mesenchymal lineages was also performed. Moreover, the gene and protein expression profiles of DPMSCs were identified by real-time polymerase chain reaction and flow cytometry techniques, respectively. Furthermore, proteins secreted by DPMSCs were detected by sandwich enzyme-linked immunosorbent assays. Finally, the proliferation and migration potentials of DPMSCs were also determined. The DPMSCs were positive for MSC markers and negative for hematopoietic and endothelial markers, as well as costimulatory molecules and HLA-DR. Functionally, DPMSCs formed colonies and differentiated into chondrocytes, osteocytes, and adipocytes. In addition, they proliferated and migrated in response to different stimuli. Finally, they expressed and secreted many biological and immunological factors with multiple functions. Here, we carry out an extensive characterization of DPMSCs of human placenta. We report that these cells express and secrete a wide range of molecules with multiple functions, and therefore, we suggest that these cells could be an attractive candidate for cell-based therapy.